Advances in Bract Coloration: Diversity, Pigment Synthesis, and Regulatory Mechanisms in Ornamental Plants - Xiaoyang Li; Yang Liu; Zhiquan Cai; Yiwei Zhou (Plants, 2025)
Bract coloration in ornamental plants is a complex trait governed by diverse pigments (chlorophylls, anthocyanins, betalains, and carotenoids), their biosynthetic pathways, and regulatory networks. While previous research has primarily focused on floral pigmentation, studies on bract coloration—particularly in species where bracts serve as the primary ornamental feature—have received less attention until recent advances. This review synthesizes current understanding of bract color diversity, pigment biochemistry, and molecular regulation in key species including Bougainvillea, Euphorbia pulcherrima, Anthurium andraeanum, Curcuma alismatifolia, and Zantedeschia hybrida. Anthocyanins predominantly contribute to red-to-purple hues, while betalains generate red, purple, or yellow coloration through differential accumulation of betacyanins and betaxanthins. Developmental color transitions are mediated by chlorophyll degradation and carotenoid dynamics. The spatiotemporal regulation of pigment accumulation involves coordinated interactions between key structural genes (CHS, DFR, ANS for anthocyanins; DODA, CYP76AD1 for betalains), transcription factors (MYB, bHLH, WRKY), and plant growth regulators (BAP, GA, MeJA). Despite these advances, significant knowledge gaps remain in genetic inheritance patterns, epigenetic regulation, cross-pigment pathway crosstalk, and environmental modulation. Future research directions should integrate multi-omics approaches, wild germplasm resources, and gene-editing technologies to develop novel breeding strategies for bract color improvement.